Down regulation of specific binding of [20-3H]phorbol 12,13-dibutyrate and phorbol ester-induced differentiation of human promyelocytic leukemia cells. - Solanki, V (1981)
Binding of [20-3H]phorbol 12,13-dibutyrate ([3H]PDB) to intact human promyelocytic leukemia cells susceptible (HL-60) or resistant (R-35) to phorbol ester-induced differentiation was characterized. Specific binding of [3H]PDB to both HL-60 and R-35 cells at 37 degrees C reached a maximum within 15-20 min. Maximal specific [3H]PDB binding to HL-60 cells was followed by a decline (down regulation) of radioactivity. This down regulation was temperature dependent, because no loss of radiolabel occurred by 1 hr at 4 degrees C. The down regulation of bound [3H]PDB seen in HL-60 cells at 37 degrees C was not observed with R-35 cells. Prior exposure of the HL-60 cells but not of R-35 cells to 1 microM phorbol 12-myristate 13-acetate for 90 min at 37 degrees C caused a marked reduction in the specific binding of [3H]PDB. When [3H]PDB binding was carried out at 4 degrees C, [3H]PDB bound to both cell types in a rapid, specific, and reversible manner. At equilibrium, HL-60 and R-35 cells were found to contain almost the same number of binding sites, which had dissociation constants of about 50 nM, indicating that the failure of R-35 cells to undergo PDB-induced differentiation was not associated with any change in the affinity or in the number of [3H]PDB binding sites. These results indicate that the down regulation of specific [3H]PDB binding may be a crucial early event in the control of phorbol ester-induced terminal differentiation in HL-60 cells. Furthermore, we suggest that such down regulation may be involved in other cellular and biochemical effects of phorbol diester tumor promoters.